A Comprehensive Investigation into the Corrosion Mechanism of an Electroless Ni–P Coating in CO2-Saturated NaCl Solution: Degradation or Penetration? - Huang, Chenhao; Yan, Jing; Fan, Hongyuan; Sun, Lan; Wang, Jun (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2024)
Electroless Ni–P coating has been validated for its exemplary corrosion resistance in the realm of oil and natural gas industries. Nevertheless, the precise corrosion mechanisms remain a subject of considerable debate and contention. In this study, we employed the variable in question, namely temperature, to emulate fluctuations in the driving forces of corrosive medium diffusion, offering an in-depth exploration into the corrosion behavior of Ni–P coatings within a saturated CO 2 milieu. Our findings elucidate that diminished driving forces predispose the coating to localized corrosion, whereas augmented driving forces enhance uniform corrosion. Moreover, the empirical evidence predominantly supports the dissolution of Ni and the deposition of PO x as the prevailing corrosion mechanisms, with the infiltration of the corrosive medium primarily contingent upon the magnitude of the diffusion-driven force, rather than the inherent nano-scale pores of the coating. Furthermore, employing in situ electrochemical analysis, we delineated the corrosion mechanisms of Ni–P coatings under varying diffusion-driven forces in this milieu and proffered a corrosion model adeptly explicating this phenomenon.